Results of STD 3 agricultural research projects summarised on CTA's website - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The third Life Sciences and Technologies for Developing Countries Programme (STD 3), funded by the European Commission, ran from 1992 to 1995. This programme encouraged research institutions of industrialised and developing countries to co-operate...